2004
DOI: 10.1074/jbc.m311688200
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Enhances Interleukin-6-induced Vascular Endothelial Growth Factor 165 Expression via Activation of Gp130-mediated p44/42 MAPK-CCAAT/Enhancer Binding Protein Signaling in Gingival Fibroblasts

Abstract: Diabetic patients are susceptible to severe inflammatory periodontitis manifesting as swollen gingiva with bleeding, but the underlying mechanism is not well understood. Our purpose was to determine the effect of a high glucose (HG) condition on the interleukin-6/soluble interleukin-6 receptor (IL-6/sIL-6R)-induced activation of signaling and vascular endothelial growth factor (VEGF) expression in human gingival fibroblasts (HGFs). In this study, HGFs were cultured for at least two passages under a normal gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 35 publications
4
36
0
Order By: Relevance
“…One important role of this phosphorylation is removal of the inhibitor histone deacetylase 3 (29). Moreover IL-6 has been reported to activate some mitogenactivated protein kinase pathways capable of phosphorylating c-Jun in certain cell types (13,22). We found that c-Jun S63,S73 phosphorylation occurs in HepG2 cells in response to IL-6 plus the soluble IL-6 receptor in a dose-dependent manner (Fig.…”
mentioning
confidence: 59%
“…One important role of this phosphorylation is removal of the inhibitor histone deacetylase 3 (29). Moreover IL-6 has been reported to activate some mitogenactivated protein kinase pathways capable of phosphorylating c-Jun in certain cell types (13,22). We found that c-Jun S63,S73 phosphorylation occurs in HepG2 cells in response to IL-6 plus the soluble IL-6 receptor in a dose-dependent manner (Fig.…”
mentioning
confidence: 59%
“…The mechanism by which VEGF regulates C/EBPβ remains unclear. However, in a recent article human gingival fibroblast when exposed to hyperglycemia, had demonstrated IL-6 induced phosphorylation of p44/p42 MAPK with subsequent CEBP nuclear translocation and VEGF 165 expression (24).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, vascular endotherial growth factor (VEGF) is a significant factor for diabetic complications, and is implicated in the development of neovascularization and endotherial dysfunction in diabetic retinopathy [13]. We showed that HG enhances IL-6/sIL-6R-induced VEGF production in HGFs [14]. A series of reports suggest that exaggerated response of HGF affected by both elevated glucose and inflammatory cytokines may lead to severe periodontitis.…”
Section: Introductionmentioning
confidence: 89%